Anti-IFN-γ Autoantibody Syndrome Presenting with Disseminated Nontuberculous Mycobacteria Infections: A Case Series of Therapeutic Implications and Review of Literature - Brooke Cheng; Barinder Bajwa; Seungwon Choi; Hannah Martin; Tyson Miao; Denise Werry; Michael Perlman; Yazdan Mirzanejad (Tropical Medicine and Infectious Disease, 2025)
Anticytokine autoantibodies (AAbs), particularly anti-interferon-gamma (anti-IFN-γ) AAbs, disrupt cytokine functions, leading to infections, autoimmune-like diseases, and conditions resembling interleukin-12 (IL-12)/IFN-γ pathway defects. Advances in genetic testing have clarified overlaps between autoinflammatory, autoimmune disorders, and primary immunodeficiencies but reveal complex phenotypes and pathways. While these insights deepen our understanding of immune mechanisms, they also complicate diagnosis and treatment, with limited options for IFN-γ deficiencies caused by genetic mutations. The adult-onset immunodeficiency with disseminated lymphadenitis due to nontuberculous mycobacteria (NTM) and other opportunistic infections has been linked to high levels of anti-IFN-γ AAbs. This syndrome, initially identified in HIV-negative Asian patients, frequently affects individuals of Asian descent and may be associated with specific human leukocyte antigen (HLA) alleles. The presence of neutralizing anti-IFN-γ AAbs impairs the IFN-γ-dependent immune response, likely contributing to the persistent NTM infection. This study underscores the potential for late-onset anti-IFN-γ AAb syndrome to manifest with disseminated NTM (dNTM) infections, highlights the importance of timely diagnosis and considers rituximab as a potential therapeutic option.